2015
DOI: 10.1002/oby.21164
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide prevents obesity in aged female mice in association with increased retinoid and estrogen signaling

Abstract: Objective: The synthetic retinoid fenretinide (FEN) inhibits adiposity in male mice fed a high-fat diet (HFD) in association with alterations in retinoic acid (RA) signaling. Young female mice are protected from obesity via estrogen signaling. We, therefore, investigated whether FEN also influences adiposity in aged female mice differing in parity and whether such effects are mediated by retinoid and estrogen signaling. Methods: Aged nulliparous and parous female mice were maintained on HFD 6 FEN, and adiposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…This mainly occurs via the inhibition of adipogenesis through prevention of C/EBPβ transcription (Mcilroy et al, ). The treatment was not expected to alter the food intake (Shearer et al, ) and, indeed, food intake was unchanged in EKO and negligibly increased in WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mainly occurs via the inhibition of adipogenesis through prevention of C/EBPβ transcription (Mcilroy et al, ). The treatment was not expected to alter the food intake (Shearer et al, ) and, indeed, food intake was unchanged in EKO and negligibly increased in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The possible effects of fenretinide treatment on body weight, fat mass accumulation, glucose metabolism and plasma lipid levels, which has yet to be tested in the EKO model, were investigated in the present study. The reduction of body weight gain following fenretinide treatment has been thoroughly documented in wild‐type and in genetically obese mice (Koh et al, ; Mcilroy et al, ; Preitner et al, ; Shearer et al, ). Consistent with these findings, in the present study fenretinide treatment was found to reduce body weight gain and fat mass in both EKO and wild‐type mice.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have recently identified FEN as a potential safe treatment for diet-induced obesity and type-2 diabetes in mice17181922. FEN can directly inhibit leptin gene transcription but does not have measureable effects on food intake or energy expenditure1718.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that FEN prevents obesity and improves insulin sensitivity in both high fat diet (HFD)-fed male and female mice171819. FEN acts via several different mechanisms including induction of retinoid signalling, increased hepatic lipid oxidation and inhibition of the final step of ceramide biosynthesis in multiple tissues to exert its metabolic effects202122.…”
mentioning
confidence: 99%
“…Fenretinide is a synthetic retinoid that is being tested in clinical trials for the treatment of breast cancer and insulin resistance, but its mechanism of action has been elusive. Data indicated that fenretinide inhibits dihydroceramide desaturase, an enzyme involved in the biosynthesis of lipotoxicceramides that antagonize insulin action (Shearer et al 2015). Because of this finding, we assessed whether fenretinide could improve insulin sensitivity and glucose homeostasis in vitro and in vivo by controlling ceramide.…”
Section: Introductionmentioning
confidence: 99%